PERFORMANCE OF MILLET SUBMITTED TO IRRIGATION DEPTHS - Frasca, Laylla Luanna de Mello (2020)
He millet (Pennisetum glaucum L.) crop presents its economic potential due to its versatility of uses in the agronomic scenario, among high potential of soil cover, rich nutrition in food and feed and source for biofuels. Despite the tolerance to water deficit, it suffers some variations in its development and productivity. Thus, the objective of this work is to evaluate the response of ADR 300 and ADR 500 cultivars submitted to several irrigation depths. The experiment was carried out in a greenhouse at the State University of Goiás at Ipameri Campus - GO. The experimental design was a completely randomized block in factorial scheme. The treatments were: A - variety of cultivar ADR 300 and B - variety of cultivar ADR 500); And in the subplots: 1- irrigation depth 50%, 2- irrigation depth 60%, 3 - irrigation depth 70%, 4- irrigation depth 80% and 5 - irrigation depth 100%, delimited through the capacity of field of each vase. Evaluating the following characteristics: plant height (ALT), stem diameter (DIA), leaf area (AFOL), leaf number (NFOL), dry matter (MS) and yield (PROD). Data were subjected to analysis of variance, and when the F test was significant, the Tukey test, with p <0.05, for the quantification of the isolated variables, while the interactions used regression p <0.05, using the SISVAR software. . Irrigation management did not show significant results for the isolated variables, and the interaction between them, characterizing that the cultivation under the cultivation conditions would not be necessary the irrigation increments. Therefore, the use of irrigation in millet crop was not significant.